Diindole[3, 2-b:4, 5-b′]pyrrole as a chromophore containing three successively fused pyrroles: synthesis, optoelectronic properties and π-functionalization. Issue 7 (18th February 2016) - Jiang, Ming-Jian; Xiao, Wen-Jing; Huang, Jin-Chang; Li, Wei-Shi; Mo, Yue-Qi
Abstract: Diindole[3, 2- b :4, 5- b ′]pyrrole (DIP ) is an interesting chromophore containing three successively fused pyrrole rings. However, its basic properties and further π-functionalization have been rarely explored. In this article, two DIP compounds with alkyl or aromatic substituents at the central N position were successfully prepared. The preliminary optoelectronic properties of them also were studied. The property of possessing two reversible oxidation redox couples also agrees with their electron-rich nature. Similar to the alkyl case, the aromatic substitution at the central N position has subtle influence onDIP basic optoelectronic properties. Furthermore, these two compounds can be easily π-modified via the attachment of various π moieties at 2, 9 or 3, 8 positions ofDIP skeleton. Compared with that at 2, 9 positions, π-functionalization at 3, 8 positions showed a much better π-extension effect. Graphical abstract: